Pengaruh Work-Life Balance Terhadap Motivasi Dampaknya Pada Produktivitas Kerja Karyawan PT. PLN Muara Karang - Putirulan, Angelita; Sumbogo, Ignatius Ario (STREAMING, 2023)
This study aims to determine the direct effect of Work-life balance on employee productivity, as well as the indirect effect of Work-life balance on employee productivity through motivation. The sampling technique in this study used non-probability sampling. This study uses a quantitative approach. The research method used in this research is path analysis with a regression technique where data collection is done by distributing questionnaires to 41 employees of PT. PLN Nusantara Power up Muara Karang. Data analysis used is the classical assumption test and hypothesis testing using the t (partial) test and the coefficient of determination (R2). The results of the questionnaire were tested using the SPSS version 26 program. The path analysis results showed that the direct path Work-life balance had a significant effect on productivity by 0.467 or 46.7%, the remaining 53.3% was influenced by other factors, while the indirect path analysis showed that Work-life balance had no effect on productivity through motivation of 375 or 37.5%, the remaining 62.5% were influenced by other factors outside this model.